Som to wyrażenia algebraiczne
1. 3x+(2x+3y)+1 =
2. 4a +(5b-4a+2) =
3. (2a+3b)+(3a-4b) =
4. (7m-5n)+(-6m+5n) =
5. (-4a+3b)-(-1+4a+3b) =
6. (-3ab+2a-3b)+(3ab-2a+3b) =
7.8m-(3m-2n+1) =
8.7a-(-2a+3b-2) =
9.-5x-(5x-5y+8) =
10.(a+b)-(2a-3b) =
11. (2m-3n)-(-5m-4n) =
12. 0-(7x+y-1)-(-8x-j+1) =
13.*(x+3y-z)-(-5x-3y+2) =

1

Odpowiedzi

2010-02-15T23:37:04+01:00
1. 3x+(2x+3y)+1 = 3x+2x+3y+1 = 5x+3y+1
2. 4a +(5b-4a+2) = 2a+5b-4a+2 = -2a+5b+2
3. (2a+3b)+(3a-4b) = 2a+3b+3a-4b = 5a-b
4. (7m-5n)+(-6m+5n) = 7m-5n-6m+5n = m
5. (-4a+3b)-(-1+4a+3b) = -4a+3b+1-4a-3b = -8a+1
6. (-3ab+2a-3b)+(3ab-2a+3b) = -3ab+2a-3b+3ab-2a+3b = 0
7. 8m-(3m-2n+1) = 8m-3m+2n-1 = 5m+2n-1
8. 7a-(-2a+3b-2) = 7a+2a-3b+2 = 9a-3b+2
9. -5x-(5x-5y+8) = -5x-5x+5y-8 = -10x+5y-8
10. (a+b)-(2a-3b) = a+b-2a+3b = -a+4b
11. (2m-3n)-(-5m-4n) = 2m-3n+5m+4n = 7m+n
12. 0-(7x+y-1)-(-8x-y+1) = -7x-y+1+8x+y-1 = x
13. (x+3y-z)-(-5x-3y+2) = x+3y-z+5x+3y-2 = 6x+6y-z-2